Strategic Management of the Ministry of Social Affairs in Promoting Self-Reliance and Prosperity Among Beneficiary Families of the Family Hope Program - Kusumaningrum, Risna; Nurlitasari, Anisa; Supriyatno, Budi; Hakim, Azis; Haposan, Christian (CV. Publikasi Indonesia, 2024)
The Family Hope Program (PKH) is a conditional cash transfer initiative in Indonesia aimed at reducing poverty and improving access to education, health, and welfare services among Beneficiary Families (KPM). Despite its success, ensuring that KPM achieve independence and prosperity remains a key challenge. This study examines the strategic management practices of the Ministry of Social Affairs in promoting self-reliance among KPM. Using a qualitative descriptive approach, data were collected through literature and documentation studies. The analysis focused on the Ministry's planning, implementation, and evaluation processes, alongside the integration of the PENA (Nusantara Economic Hero) empowerment program. Findings reveal that the Ministry employs strategic management from data collection and program distribution to monitoring and evaluation. The PENA program, targeting entrepreneurial development, has enhanced the capacity of KPM to achieve economic independence. However, gaps in resource accessibility and program coverage persist. The study concludes that while strategic management significantly contributes to the effectiveness of PKH, expanding empowerment initiatives and fostering inter-agency collaboration are crucial for achieving broader impacts. Recommendations include extending the PENA program and conducting comprehensive evaluations to guide future policy enhancements.